Analisis Komparasi Penggunaan Metode MACD, Moving Average, dan Stochastic dalam Optimalisasi Profit - Abdul Chotib Nasih; Siti Ridloah (The Indonesia Capital Market Institute, 2021)
The purpose of this study is to make decisions on the right time to buy and sell shares on IDX 30 by using technical analysis including MACD, moving average, and stochastic oscillator. This research is a descriptive qualitative research. The population of this study is companies listed on IDX30 for the 2017-2019 period. Sampling was done by using purposive sampling technique. Research locations on stocks listed on IDX30 using the AmiBroket Chart software. Data analysis uses technical analysis using three indicators, namely MACD, moving average, and stochastic oscillator. Based on the research results of the three indicators, MACD generates the greatest profit. The right moment (giving a buy signal) in using MACD is when the MACD line crosses the signal line from the bottom up or Golden Cross as a bullish trend. A condition that gives a sell signal if the MACD line crosses the signal line from up to down or Death Cross is a bearish trend.